Analysis of Multicultural Counseling and Social Justice Competencies Framework amid Cultural Diversity for Counselor Professionalism in Indonesia - Moch. Syihabudin Nuha; Muhammad Ali Najich; Miftahul Jannah; Moch. Syihabudin Nuha; Muhammad Ali Najich; Miftahul Jannah (Universitas Negeri Malang, 2026)
The increasing cultural diversity in social life necessitates that counselors possess adequate multicultural competencies to effectively serve clients from various backgrounds. Considering a client's cultural context is essential to prevent bias and stereotypes, thereby enhancing counselor professionalism when addressing the diversity inherent in each student. This study aims to explore and analyze the importance of multicultural counseling competencies for counselors by reviewing existing literature. The primary objective is to synthesize findings from previous research to highlight key competency frameworks relevant to contemporary practice. This research employs a Systematic Literature Review (SLR) method. The study analyzed 30 journal articles, consisting of 14 international and 16 national journals from the 2013-2023 period. Literature was obtained through a systematic Google Scholar search using the keyword